Analisis Program Alokasi Dana Desa (ADD) Dalam Pemberdayaan Masyarakat Desa Di Desa Bangun Sari Deli Serdang Tahun 2018 - Disa Devalia Rizki Aranda Lubis; Abdul Kadir; Yurial Arief Lubis (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2022)
Program Alokasi Dana Desa (ADD) is an implementation Alokasi Dana Desa through physical and no-physical development. This research background by program Alokasi Dana Desa (ADD) in empowering village communities at Desa Bangun Sari namely the KDRT prevention program that was established in 2018 where this program could not be realized with a total of Rp 41.000.000-, funds. This study aims to analyze the program Alokasi Dana Desa in the empowerment of rural communities, namely the KDRT program and what are the obstacles for not realizing the program. As for the method used in this study is a descriptive qualitative method. In this study, researchers used three informants who knew as well additional informants. There are two ways to collect data, namely secondary data such as book, journals and documentation, while primary data such as interview and observation. From the result of the above research it can be seen that the program analysis Alokasi Dana Desa (ADD) in empowering village communities at Desa Bangun Sari in 2018 not maximal enough in its application which cab ve examined throught three program indicators according to chareles, namely organizing, interpretation and application.